Population Pharmacokinetics and Model-Based Dosing Optimization of Teicoplanin in Pediatric Patients - Zhang, Tao; Sun, Dan; Shu, Zuocheng; Duan, Ziyun; Liu, Yang; Du, Qian; Zhang, Ying; Dong, Yuzhu; Wang, Taotao; Hu, Sasa; Cheng, Hua; Dong, Yalin (Frontiers in Pharmacology, 2020)
Objectives: The pharmacokinetics (PK) of teicoplanin differs in children compared with adults. Our aim was to determine the PK of teicoplanin in an Asian pediatric population and to optimize dosage regimens. Methods: This was a retrospective PK study and all the data were collected from hospitalized children. We developed a population PK model using sparse data, and Monte Carlo simulation was used to assess the ability of standard teicoplanin regimen and other different dosage regimens. The optimal dosing regimens were defined as achieving the target trough concentration (Cmin) of 10 mg/L and pharmacokinetic/pharmacodynamic (PK/PD, [AUC24/MIC]) of 125 for moderate infection. For severe infection, the optimal dosing regimens were defined as achieving the target 15 mg/L and AUC24/MIC of 345. Results: 159 children were included and 1.5 samples/children on average were provided. Estimated clearance of teicoplanin was 0.694 L/h (0.784/L/h/70 kg) and volume of distribution was 1.39 L. Teicoplanin standard loading dose was adequate for moderate infection, while 13 mg/kg was needed for severer infection. With standard maintenance doses, both patients with moderate and severe infection failed to achieve the target Cmin. 12 and 16 mg/kg/day were required to achieve a Cmin ≥ 10 and 15 mg/L, respectively. However, standard maintenance dose was adequate to achieve AUC24/MIC ≥ 125 for moderate infection, and 12 mg/kg/day was needed to achieve AUC24/MIC ≥ 345 for severe infection. Lower weight and serum creatinine were associated with higher dose. Conclusion: Optimal doses based on the target Cmin were higher than that based on the PK/PD target. To achieve the Cmin and PK/PD targets simultaneously, a standard loading dose was adequate for moderate infection based on simulation, while dosing higher than standard doses were required in other situation. Further clinical studies with rich sampling from children is required to confirm our findings.